Intrahippocampal Administration of Ibotenic Acid Induced Cholinergic Dysfunction via NR2A/NR2B Expression: Implications of Resveratrol against Alzheimer Disease Pathophysiology - Karthick, Chennakesavan; Periyasamy, Sabapathy; Jayachandran, Kesavan S.; Anusuyadevi, Muthuswamy (Frontiers in Molecular Neuroscience, 2016)
Although several drugs revealed moderate amelioration of symptoms, none of them have sufficient potency to prevent or reverse the progression towards Alzheimer’s disease (AD) pathology. Resveratrol (RSV), a polyphenolic compound has shown an outstanding therapeutic effect on a broad spectrum of diseases like age-associated neurodegeneration, inflammation etc. The present study was thus conducted to assess the therapeutic efficacy of RSV in ameliorating the deleterious effects of Ibotenic acid (IBO) in male Wistar rats. Stereotactic intrahippocampal administration of IBO (5µg/µl) lesioned rats impairs cholinergic transmission, learning and memory performance that is rather related to AD and thus chosen as a suitable model to understand the drug efficacy in preventing AD pathophysiology. Since IBO is an agonist of glutamate, it is expected to exhibit an excitotoxic effect by altering glutamatergic receptors like NMDA receptor. The current study displayed significant alterations in the mRNA expression of NR2A and NR2B subunits of NMDA receptors, and further it is surprising to note that cholinergic receptors decreased in expression particularly α7-nAChR with increased m1AChR. RSV administration (20mg/kg body weight, i.p) significantly reduced these changes in IBO induced rats. Glutamatergic and cholinergic receptor alterations were associated with significant changes in the behavioral parameters of rats induced by IBO. While RSV improved spatial learning performance, attenuated immobility and improvised open field activity in IBO induced rats. NR2B activation in the present study might mediate cell death through oxidative stress that form the basis of abnormal behavioral pattern in IBO induced rats. Interestingly, RSV that could efficiently encounter oxidative stress have significantly decreased stress markers viz., nitrite, PCO, and MDA levels by enhancing antioxidant status. Histopathological analysis displayed significant reduction in the hippocampal pyramidal layer thickness and live neurons in IBO induced rats, with slight pathological changes in the entorhinal cortex (EC) of rat brain, which was prevented on RSV administration. Our study thus concludes that RSV administration significantly ameliorated the deleterious effects in the IBO lesioned rat model for AD by alleviating cholinergic pathways, reducing oxidative stress and thereby improving spatial memory.